Elementos de um crime: a narrativa da literatura policial no podcast O Caso Evandro - Silva, Jonatan Rafael da (2023)
This work aims to address the correlations and crossings of the narrative of police literature in the podcast O Caso Evandro, a program that focused on the death of the boy Evandro Ramos Caetano, aged 6, in Guaratuba, on the coast of Paraná, in 1992, in addition to contesting the investigations into the crime, which resulted in the arrest of seven innocent people. So, we sought to explore a theoretical basis capable of giving shape to the understanding of what detective literature is, as a literary movement and also a cultural response to the modernization of metropolises, especially Paris. Among the authors who examine the narrative genre are P. D. James, an important name in detective literature, Ricardo Piglia, Umberto Eco, Jorge Luis Borges. Julio Cortázar – who also dedicated themselves to literature and explored detective fiction within their artistic production –, and also the theorists Tzvetan Todorov, Roland Barthes, Claude Bremond, Terry Eagleton, Michel Butor and Michel Foucault. In order to understand the interface between literature and urban space, this dissertation drew on the views of Walter Benjamin, Charles Baudelaire, Clóvis Gruner, Bruno Paes Manso, Marshall Berman and David Harvey. To create an archeology of true crime, responsible for portraying and retelling real crimes both in podcasts and in other languages such as cinema, literature, etc., the works of Truman Capote, considered the founding father of the genre, and Carol Moreira and Mabê Bonafé. Discussing detective literature itself, Edgar Allan Poe was chosen, like its creator, Raymond Chandler, to show the evolution of the narrative and also the figure of the detective. As a way of analyzing the discourse of O Caso Evandro, 14 podcast episodes were selected and observed using Laurence Bardin’s methodology. Therefore, this work is divided as follows: in Chapter 1, the idea of modernity and the transformations taking place in the city are investigated; Chapter 2 is dedicated to police literature, its historiography, aesthetics and developments; while Chapter 3 takes up police literature based on its language; in Chapter 4 the podcast media is analyzed, reviewing its history and particularity, genres and massification; Chapter 5 is dedicated to O Caso Evandro, discussing the program presented by Ivan Mizanzuk and also the crime and the issues surrounding it; In Chapter 6, the program is analyzed and all the precepts presented in the third chapter are discussed.